High school students’ 21st-century learning skills in organic chemistry group learning - Sa-ngiemjit, Maneerat; Vázquez-Alonso, Ángel; Manassero-Mas, María-Antonia (Institute of Advanced Engineering and Science, 2025)
Children with 21st-century learning abilities thrive in today’s globalized world, underscoring the importance of early skill development by both schools and parents. This study aims to evaluate high school students’ grasp of organic chemistry in relation to critical thinking, creativity, communication, and collaboration skills. Conducted with 15 groups of grade 12 students in science-mathematics, the research employed a mixed-methods approach, combining written surveys and observations. Statistical tools such as averages, standard deviations, and correlation coefficients were utilized for data analysis, followed by specific statistical tests to ensure validity and significance. Correlation analysis was used to examine the relationships between each 21st-century learning skill. Findings indicate that in organic chemistry, students hone critical thinking through data evaluation, and problem-solving, while fostering creativity in molecule synthesis and solution-finding. Effective communication fosters collaboration and teamwork, essential for achieving common goals. Average scores from writing surveys for critical thinking, creativity, and communication were 1.62, 1.65, and 1.68, respectively, with collaboration evaluated through observation scoring 2.03. Notably, a significant positive correlation was found between each skill, indicating that enhancing one skill often leads to improvements in the others. This highlights the importance of a holistic approach to developing 21st-century educational abilities.